2014
DOI: 10.1111/ele.12316
|View full text |Cite
|
Sign up to set email alerts
|

Global mismatch between species richness and vulnerability of reef fish assemblages

Abstract: The impact of anthropogenic activity on ecosystems has highlighted the need to move beyond the biogeographical delineation of species richness patterns to understanding the vulnerability of species assemblages, including the functional components that are linked to the processes they support. We developed a decision theory framework to quantitatively assess the global taxonomic and functional vulnerability of fish assemblages on tropical reefs using a combination of sensitivity to species loss, exposure to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 48 publications
(62 reference statements)
7
105
0
Order By: Relevance
“…Finally, for some of the same reasons that fueled disputes for terrestrial ecosystems, hotspots on coral reefs (Roberts et al, 2002) have also been the subject of controversy (Briggs, 2002;Hughes et al, 2002). In this respect, Parravicini et al (2014) have recently identified tropical reef areas that are critical for preventing the loss of fish taxonomic and functional biodiversity. These areas, such as the Western Indian Ocean, differ in important ways from the fish richness hotspots previously identified close to the Indo-Australian Archipelago.…”
Section: Criticism Of Biodiversity Hotspotsmentioning
confidence: 99%
“…Finally, for some of the same reasons that fueled disputes for terrestrial ecosystems, hotspots on coral reefs (Roberts et al, 2002) have also been the subject of controversy (Briggs, 2002;Hughes et al, 2002). In this respect, Parravicini et al (2014) have recently identified tropical reef areas that are critical for preventing the loss of fish taxonomic and functional biodiversity. These areas, such as the Western Indian Ocean, differ in important ways from the fish richness hotspots previously identified close to the Indo-Australian Archipelago.…”
Section: Criticism Of Biodiversity Hotspotsmentioning
confidence: 99%
“…The null hypothesis of no correlation between maximum intraspecific K2P distance and SL, PLD or GRS was tested using Pearson's R test as implemented in the R Stats v. 3.1.2 package (R Core Team 2014). GRS was estimated based on species occurrences across an Indo-Pacific 5° × 5° grid from Parravicini et al (2014) and expressed in terms of the number of cells in which a species occurs. SL data were collected from FishBase (Froese & Pauly 2016), and PLD data were obtained from Luiz et al (2013).…”
Section: Lhts and Genetic Divergencementioning
confidence: 99%
“…The WIO has several characteristics and challenges that make it unique and a global priority for conservation and sustainable management (Allen 2008;McClanahan & Cinner 2012;Parravicini et al 2014;Worm & Branch 2012). This may be achieved by expanding the MPAs through international collaboration, but these plans need to be considered in the context of the challenges related to environmental change, subsistence economies, poor fisheries-dependent coastal populations and the international composition of the pelagic fisheries industry.…”
Section: Resultsmentioning
confidence: 99%
“…WIO coral reefs support many people that rely primarily on natural resources, and this results in a range of intense human use and environmental impacts such as unsustainable fishing and sedimentation (Hicks 2011;Maina et al 2013;Parravicini et al 2014;UNEP-Nairobi Convention & WIOMSA 2015;van der Elst et al 2005). Coral reefs are threatened by both oceanic and land-derived factors; thus, landsea connections play an important role in the sustainable use and biodiversity conservation (Klein et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation